(untitled) (Journal of Dhaka Medical College, 2025)
Background: Growing pains is the most common benign unexplained limb pain in childhood that tends to self-limit once the child reaches adolescence. The present study aimed to get the details knowledge and compare different demographic and clinical characteristics of growing pains (GP). Methods: This cross-sectional study was conducted from August 2021 to September 2022 at National Centre for Control of Rheumatic Fever and Heart Diseases, Dhaka, Bangladesh. Children of 3-12 years irrespective of sex with unexplained limb pain suspected of growing pains were included in the study. Suspicion of growing pains was based on inclusion criteria and exclusion criteria from the definition of Peterson. By collaboration of clinical history, detailed physical examination, result of relevant laboratory and radiological tests confirmatory diagnosis was made. Findings: Among 220 children with unexplained limb pain 73.2% were diagnosed clinically as growing pains. Boys were predominant (52.2%) among children with GP; 60.9% of them were between 5 to 8 years and the mean age was 7.05±2.32 years. The pain was mostly bilateral and calf muscles were the most common sites. Pain was more frequent at night and half of the children complained about pain occurring several times a week. Massaging was the most effective measure followed by oral anti-inflammatory analgesics for pain relieving. The pain was associated with daytime over-activity and a history of GP among siblings. Conclusion: Growing pains was diagnosed among three-fourths of children with unexplained limb pain. Daytime over-activity, obesity, and a positive family history may be the potential risk factors. Demographic and clinical characteristics of growing pains in the Bangladeshi paediatric population were typical as reported in other studies. J Dhaka Med Coll. 2023; 32(2) : 117-123